1999
DOI: 10.1046/j.1460-9568.1999.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate and lactate protect striatal neurons against N‐methyl‐d‐aspartate‐induced neurotoxicity

Abstract: A sustained release of glutamate contributes to neuronal loss during cerebral ischaemia. Using cultured mouse striatal neurons, we observed that glucose deprivation, which occurs in this pathological process, enhanced the N-Methyl-D-aspartate (NMDA)- or alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA)-induced neurotoxicity. The end products of glycolysis, lactate and pyruvate, strongly protected neurons from these neurotoxic effects. The neuroprotective effect of pyruvate (which is more prominent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 45 publications
5
60
1
1
Order By: Relevance
“…Indeed, a recently study also suggested that cytoprotection could be afforded even when pyruvate was provided 1-3 hr after H 2 O 2 insult in primary cortical neurons [38]. Moreover, pyruvate protection is not limited to H 2 O 2 -induced cytotoxicity, and has been demonstrated in response to various cytochemical insults, including zinc [27], menadion [13], NMDA [32], glutamate [42], β-amyloid [1], and 1-methy-4-phenylpyridinium ion (MPP+) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recently study also suggested that cytoprotection could be afforded even when pyruvate was provided 1-3 hr after H 2 O 2 insult in primary cortical neurons [38]. Moreover, pyruvate protection is not limited to H 2 O 2 -induced cytotoxicity, and has been demonstrated in response to various cytochemical insults, including zinc [27], menadion [13], NMDA [32], glutamate [42], β-amyloid [1], and 1-methy-4-phenylpyridinium ion (MPP+) [33].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, pyruvate protects against NMDA or zinc-mediated cell death by enhancing energy metabolism (Maus et al, 1999;Sheline et al, 2000). In addition, pyruvate increases neuronal survival against hydrogen peroxide (Desagher et al, 1997) and cysteine-mediated oxidative stress (Wang and Cynader, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…23) In fact, recent studies have indicated that caloric restriction and intermittent fasting suppress cumulative oxidative stress and induce neurotrophic factor. [24][25][26] Additionally, the down-regulation of PDHE1 mRNA expression might increase a pyruvate that protects neurons against hydrogen peroxide, 27) NMDA, 28) or quinolinic-induced toxicity. 29) Further investigation will be needed to examine these possibilities for the protective roles via PDHE1.…”
Section: Discussionmentioning
confidence: 99%